Didactic Principles and Instructional Design For Distance Language Learning: A Contemporary Pedagogical Framework - Babaniyazova, Nargiza (Innovative Technologica: Methodical Research Journal, 2025)
This article explores the theoretical and instructional underpinnings of distance learning with a specific focus on foreign language education. It examines constructivist, connectivist, and humanistic foundations, highlighting pedagogical advantages and limitations. Additionally, the article outlines effective instructional design models, including ADDIE and SAM, supported by cognitive theories and Bloom's taxonomy. Empirical data from global and regional contexts reinforce the practical relevance of the theoretical framework. Illustrative tables and figures are included to support the comparative and conceptual analysis.c